The Method of Restoring Lost Information from Sensors Based on Auto-Associative Neural Networks - Vladov, S. I.; Владов, С. І.; Yakovliev, R. P.; Яковлєв, Р. П.; Vysotska, V.; Nazarkevych, M.; Lytvyn, V.; Serhii Vladov (Applied System Innovation. – 2024. – Vol. 7, Isseu 3. – Article 53, 2024)
The research aims to develop a neural network-based lost information restoration method when the complex nonlinear technical object (using the example of helicopter turboshaft engines) sensors fail during operation. The basis of the research is an auto-associative neural network (autoencoder), which makes it possible to restore lost information due to the sensor failure with an accuracy of more than 99%. An auto-associative neural network (autoencoder)-modified training method is proposed. It uses regularization coefficients that consist of the loss function to create a more stable and common model. It works well on the training sample of data and can produce good results on new data. Also, it reduces its overtraining risk when it adapts too much to the training data sample and loses its ability to generalize new data. This is especially important for small amounts of data or complex models. It has been determined based on the computational experiment results (the example of the TV3-117 turboshaft engine) that lost information restoration based on an auto-associative neural network provides a data restoring error of no more than 0.45% in the case of single failures and no more than 0.6% in case of double failures of the engine parameter registration sensor event.

Метою дослідження є розробка нейромережевого методу відновлення втраченої інформації при виході з ладу сенсорів складного нелінійного технічного об’єкта (на прикладі турбовальних двигунів гелікоптера) під час роботи. В основі дослідження лежить автоасоціативна нейронна мережа (автокодер), яка дозволяє відновлювати втрачену інформацію внаслідок несправності датчика з точністю понад 99%.

Целью исследования является разработка метода восстановления утерянной информации на основе нейронной сети при выходе из строя датчиков сложного нелинейного технического объекта (на примере вертолетных турбовальных двигателей) в процессе эксплуатации.
Keywords: Україна; Техніка. Технічні науки. Machinery. Engineering. Техника. Технические науки; publikatsii u WoS; associative neural network; autoencoder; regularization coefficients; helicopter turboshaft engines; restoring; lost information restoration; error; training; асоціативна нейронна мережа; автокодувальник; коефіцієнти регуляризації; вертолітні турбовальні двигуни; відновлення втраченої інформації; помилка; навчання; вертольот; ассоциативная нейронная сеть; вертолетные турбовальные двигатели; восстановление утерянной информации